Biodegradation and Bioremediation of Polluted Systems New Advances and Technologies - Chamy, Rolando; Rosenkranz, Francisca; Soler, Lorena (IntechOpen, 2015)
This book contains a collection of research works focused on the biodegradation of different types of pollutants, both in water and solids. The book is divided in three major sections: A) Biodegradation of organic pollutants in solids and wastewater, B) Biodegradation of complex pollutants, and C) Novel technologies in biodegradation and bioremediation.